The safety of enoxaparine use in elderly with acute myocardial infarction - Despotović Nebojša; Lončar Goran; Nikolić-Despotović Maja; Ilić Marjan; Dimković Siniša (Vojnosanitetski Pregled)
Background/Aim. Enoxaparin (ENOX), the lowmolecular- weight heparin, used in acute myocardial infarction (AMI) could lead to hemorrhage. The aim of this study was to determine whether bleeding was more often in AMI patients older than 65 or 75 years who receive ENOX or unfractionated heparin (UFH). Methods. Among the patients with AMI hospitalized during three successive months receiving ENOX or UFH, three group of parameters were investigated: demographic, ischemic and bleeding TIMI criteria. Results. Among 85 hospitalized patients with signs of AIM, there were 35 (41.2%) old 65 years or less, 32 (38.5) old 66-75 years and 18 (21.2%) older than 75 years. In AMI elderly patients, according to the received ENOX/UFH: ischemic complication (18.2 vs. 21.4%) were insignificantly lower and the number of lethal outcomes (18,2 vs. 17,8%) were insignificantly more often in ENOX group; represented only by one patient (age beyond 75 years), major and non-major bleeding events occurred only in UFH group. Conclusion. The ENOX usage in AMI in patients older than 65 years did not show any significant difference in efficacy and bleeding rate comparing to UFH.